Nickel-catalyzed CH trifluoromethylation of pyridine N-oxides with Togni's reagent. Issue 16 (18th April 2018) - Gao, Xianying; Geng, Yang; Han, Shuaijun; Liang, Apeng; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Graphical abstract: Highlights: The first nickel-catalyzed CH trifluoromethylation of pyridine N -oxides with Togni's reagent. 2-CF3 pyridine derivatives are obtained by one-step. Tolerance of a wide range of substituents under mild conditions. Abstract: The first nickel-catalyzed CH trifluoromethylation of pyridine N -oxides with Togni's reagent has been achieved. Trifluoromethylation proceeds smoothly under mild conditions with moderate functional group compatibility. Notable advantages of this method include the using of low cost of nickel catalyst, and its simple convenient operation.